Relationship between characteristics on magnetic resonance imaging and motor outcomes in children with cerebral palsy and white matter injury. (October 2015) - Reid, Susan M.; Ditchfield, Michael R.; Bracken, Jenny; Reddihough, Dinah S.
Highlights: Symmetrical involvement, extensive WM loss in the hemispheres and corpus callosum, and cerebellar involvement predicted poor gross motor function and quadriplegia. Variability in motor outcomes was not well explained by abnormalities on conventional MRI. Unilateral lesions were more likely to be focal and located more anteriorly than bilateral lesions. The relative proportions of asymmetrical/unilateral WMI increased by year of birth. Abstract: In a population cohort of children with white matter injury (WMI) and cerebral palsy (CP), we aimed to describe the magnetic resonance imaging (MRI) characteristics, identify key structure–function relationships, and classify the severity of WMI in a clinically relevant way. Stratified on MRI laterality/symmetry, variables indicating the extent and location of cerebral abnormalities for 272 children with CP and WMI on chronic-phase MRI were related to gross motor function and motor topography using univariable and multivariable approaches. We found that symmetrical involvement, severe WM loss in the hemispheres and corpus callosum, and cerebellar involvement were the strongest predictors of poor gross motor function, but the final model explained only a small proportion of the variability. Bilateral, extensive WM loss was more likely to result in quadriplegia, whereas volume loss in the posterior-mid WM more frequently resulted in diplegia. The extent and location of MRI abnormalities differed according to laterality/symmetry; asymmetry was associated with less extensive hemispheric involvement than symmetrical WMI, and unilateral lesions were more focal and located more anteriorly. In summary, laterality/symmetry of WMI, possibly reflecting different pathogenic mechanisms, together with extent of WM loss and cerebellar abnormality predicted gross motor function in CP, but to a limited extent.